Coking coal blending method for blending ultra-high vitrinite coking coal

Through the microscopic analysis of coal rock and coke, the compatibility of ultra-high scopic coking coal is accurately determined, and combined with the regulation of coal types, the problem of difficult to effectively utilize ultra-high scopic coking coal in the existing technology is solved, and the preparation of high-strength coking coal and the reduction of coking costs are achieved.

CN119899685APending Publication Date: 2025-04-29ANGANG STEEL CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510093584.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing coking coal mixing technology is difficult to effectively utilize ultra-high mirror mass coking coal, resulting in fluctuations in coking quality and high coal mixing costs.

Method used

Through coal rock analysis and coke microscopic analysis, the coking compatibility of ultra-high microscopic coking coal is accurately judged, and coal is mixed with the regulation of coal types to prepare high-intensity coke.

Benefits of technology

The efficient utilization of ultra-high mirror quality coking coal is achieved, which reduces coking costs and improves the quality stability of coke.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899685A_ABST
    Figure CN119899685A_ABST
Patent Text Reader

Abstract

The invention relates to a coking coal blending method for blending ultrahigh vitrinite coking coal. The method comprises the following steps: 1) determining the average maximum reflectivity of vitrinite and drawing a reflectivity distribution diagram; 2) quantitative analysis of coal rock macerals; (3) coal rock coal blending parameters are calculated; (4) regulating and controlling coal type screening; 5) coal blending and coking experiment; (6) inspecting the coal blending effect; and 7) industrial production verification. According to the method, coal rock analysis and coke microscopic analysis means are combined, the coking compatibility of the ultra-high vitrinite coking coal is accurately judged, and the high-strength coke is prepared on the basis; the source of the coking coal is expanded, and the coking cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coking, and in particular to a method for blending coking coal by adding ultra-high vitrinite coking coal. Background Art

[0002] More than 90% of the world's coke is used for blast furnace ironmaking. Metallurgical coke is an indispensable fuel and raw material for blast furnace ironmaking. In the ironmaking process, coke is used as a fuel to provide heat for the smelting process, and as the main reducing agent. At the same time, it maintains the air permeability of the material column in the blast furnace so that the blast furnace can operate normally. At present, 0.4 to 0.6 tons of coke are consumed to produce 1 ton of pig iron.

[0003] my country's current coal blending technology mainly relies on empirical coal blending methods, which classify coking coals such as gas coal, gas fat coal, 1 / 3 coking coal, fat coal, coking coal, and lean coal into different categories, and design the proportions according to different categories. However, the characterization of coking coal is not detailed enough, and the properties of coals in the same category are only roughly the same, resulting in low coal blending accuracy. In addition, due to the serious coal mixing, the coking characteristics of the same type of coal vary greatly, which greatly interferes with the coal blending work and ultimately leads to fluctuations in coke quality.

[0004] The coal-rock blending method based on the microscopic characteristics of coal coke treats each type of coal as a natural mixed coal. The coking coal blending process is to control the fusible components and inert components in the blended coal to an appropriate ratio. According to the coal-rock blending theory, coking coal can be divided into vitrinite, exinite, inertinite and minerals. In the coking process, different microscopic components in coking coal have different activities. It is generally believed that vitrinite and exinite are active components in coking coal, and inertinite and minerals are inert components in coking coal. The content of microscopic components in coking coal is closely related to the coking characteristics, and is also one of the basic parameters for coal-rock blending.

[0005] With the continuous consumption of high-quality coking coal resources, coking coal that was originally unsuitable or had poor use effect (such as ultra-high vitrinite coking coal) has also been tried for coking coal blending. The traditional coal blending theory is extremely poorly applicable to ultra-high vitrinite coking coal. When blending coal, the empirical coal blending method is used as a guide. The bonding index (G value) and gelatinous layer index (Y value) of ultra-high vitrinite coking coal are excellent, and the plasticity range is extremely wide. It can play the role of fat coal and be used as a skeleton coal. However, due to the abnormally high activity-inertness ratio of ultra-high vitrinite coking coal, strong mineral catalytic activity, special coke optical organization and pore structure, the coke dissolution rate is fast and the thermal strength is low.

[0006] In summary, ultra-high vitrinite coking coal has distinct coal quality characteristics, and there are certain differences in the coking characteristics of typical coking coal, and its compatibility with typical coking coal is extremely poor. Therefore, it is necessary to develop a more applicable coking coal blending method for ultra-high vitrinite content coking coal. Summary of the invention

[0007] The present invention provides a method for coking coal blending by adding ultra-high vitrinite coking coal, combines coal rock analysis and coke microscopic analysis methods to accurately judge the coking compatibility of ultra-high vitrinite coking coal, and prepares high-strength coke on this basis; the source of coking coal is expanded, which is beneficial to reducing the coking cost.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for coking coal blending by adding ultra-high vitrinite coking coal comprises the following steps:

[0010] 1) Determine the average maximum reflectance of vitrinite and draw a reflectance distribution diagram;

[0011] 2) Quantitative analysis of coal and rock microscopic components;

[0012] Determine the contents of vitrinite V, inertinite I and exinite E in ultra-high activity coking coal;

[0013] 3) Calculation of coal-rock blending parameters;

[0014] According to the metamorphic degree of ultra-high vitrinite coking coal Calculate the ideal inert component content;

[0015] 4) Regulate the selection of coal types;

[0016] The regulated coal types are divided into high metamorphic coal, low activity coal and low metamorphic coal. Each type of regulated coal is subjected to steps 1) to 3) to measure the average maximum reflectance of vitrinite and the content of microscopic components of coal rock, and the mass corresponding to the ideal inertinite content is calculated according to the relationship between the degree of metamorphism and the optimal activity-inertinite ratio;

[0017] 5) Coal blending coking experiment;

[0018] Using experimental coke ovens, ultra-high vitrinite coking coal and one of the regulated coals were blended, and binary blending coking experiments were conducted. The blending amounts of ultra-high vitrinite coking coal and regulated coal were calculated according to the amount of coal fed into the furnace.

[0019] 6) Coal blending effect inspection;

[0020] After the coal blending experiment is completed, select representative coke blocks, crush them to a particle size of less than 1.0 mm, then screen out fine particles with a particle size of less than 0.1 mm, take coke samples with a particle size of 0.1 to 1.0 mm and mix them with a binder to make blocks with a diameter of ≥ 20 mm, and prepare coke slices through coarse grinding, fine grinding and polishing; place the coke slices under a reflected polarizing microscope, insert a gypsum inspection board under orthogonal polarization, and use an oil-immersed objective to observe the coke interface bonding and microscopic characteristics. The coke with good interface bonding and small pores is regarded as a coal with good compatibility;

[0021] 7) Industrial production verification;

[0022] The ultra-high vitrinite coking coal and the regulated coal are mixed according to the proportion and used as the test coal. Industrial coal blending experiments are carried out according to the corresponding coal types to verify the production and use effects.

[0023] In the step 1), according to GB / T 6948-2008 "Method for Microscopic Determination of Vitrinite Reflectance of Coal", the maximum reflectance of the vitrinite of ultra-high activity coking coal is tested, the number of test points is not less than 100, and the mean μ and standard deviation σ of the test data are calculated; the average maximum reflectance of the vitrinite Taking the reflectivity interval of 0.10% as the step, the percentage content of the measuring points in each step was counted, and the vitrinite reflectivity distribution diagram was drawn.

[0024] In the step 5), when conducting the binary coal blending experiment, the regulated coals are first crushed and screened, and regulated coals with a particle size of 0.5-1.0 mm and less than 0.50 mm are blended in a mass ratio of 1:2.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The coking effect of ultra-high vitrinite coking coal is poor, and its price is significantly lower than that of conventional coking coal. The use of ultra-high vitrinite coking coal to prepare coke can significantly reduce the cost of coal blending, which is extremely beneficial to coking enterprises in reducing costs and increasing efficiency. The present invention combines coal rock analysis and coke microscopic analysis methods to accurately determine the coking compatibility of ultra-high vitrinite coking coal, and prepares high-strength coke on this basis; it expands the source of coking coal, which is beneficial to reducing coking costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a relationship diagram between the degree of deterioration (V-Step) and the optimal activity-inertness ratio described in the present invention.

[0028] Figure 2 This is a distribution diagram of the vitrinite reflectance of the ultra-high vitrinite coking coal A of the present invention.

[0029] Figure 3a The optical structure characteristics of the ultra-high vitrinite coking coal A and high metamorphic coal blended into coke Figure 1 .

[0030] Figure 3b The optical structure characteristics of the ultra-high vitrinite coking coal A and high metamorphic coal blended into coke Figure 2 .

[0031] Figure 4 This is a distribution diagram of the vitrinite reflectance of the ultra-high vitrinite coking coal B described in the present invention.

[0032] Figure 5aThe optical structure characteristics of the ultra-high vitrinite coking coal B and low activity coal blended into coke according to the present invention Figure 1 .

[0033] Figure 5b The optical structure characteristics of the ultra-high vitrinite coking coal B and low activity coal blended into coke according to the present invention Figure 2 .

[0034] Figure 6 This is a distribution diagram of the vitrinite reflectance of the ultra-high vitrinite coking coal C of the present invention.

[0035] Figure 7a The optical structure characteristics of the ultra-high vitrinite coking coal C and low metamorphic coal blended into coke according to the present invention Figure 1 .

[0036] Figure 7b The optical structure characteristics of the ultra-high vitrinite coking coal C and low metamorphic coal blended into coke according to the present invention Figure 2 .

[0037] Figure 8a The microscopic characteristics of the coke prepared by coking the ultra-high vitrinite coking coal A described in the present invention alone are Figure 1 .

[0038] Figure 8b The microscopic characteristics of the coke prepared by coking the ultra-high vitrinite coking coal A described in the present invention alone are Figure 2 .

[0039] Figure 9a The microscopic characteristics of the coke prepared by coking the ultra-high vitrinite coking coal B described in the present invention alone are Figure 1 .

[0040] Figure 9b The microscopic characteristics of the coke prepared by coking the ultra-high vitrinite coking coal B described in the present invention alone are Figure 2 .

[0041] Fig.10a The microscopic characteristics of the coke prepared by coking the ultra-high vitrinite coking coal C alone are as follows: Figure 1 .

[0042] Fig.10b The microscopic characteristics of the coke prepared by coking the ultra-high vitrinite coking coal C alone are as follows: Figure 2 . DETAILED DESCRIPTION

[0043] The method for coking coal blending by adding ultra-high vitrinite coking coal of the present invention comprises the following specific steps:

[0044] 1. Determine the average maximum reflectivity of vitrinite and draw a reflectivity distribution diagram;

[0045] According to GB / T 6948-2008 "Method for Determination of Coal Vitrinite Reflectance by Microscope", the maximum reflectance of vitrinite of ultra-high activity coking coal is tested, the number of test points is not less than 100, and the mean μ and standard deviation σ of the test data are calculated; the average maximum reflectance of vitrinite

[0046] Taking the reflectivity interval (order) of 0.10% as the unit, the percentage content of the measuring points of each order was counted respectively, and the vitrinite reflectivity distribution diagram was drawn.

[0047] 2. Quantitative analysis of coal and rock microscopic components;

[0048] The contents of vitrinite V, inertinite I and exinite E in ultra-high activity coking coal were tested.

[0049] 3. Calculation of coal-rock blending parameters;

[0050] According to the theory of coal-rock blending, the active components of coking coal are not as high as possible, but need to maintain a certain ratio, namely the optimal active-inert ratio.

[0051] According to the coal-rock blending theory, based on the metamorphic degree of ultra-high vitrinite coking coal An example of calculating the ideal inert component content is shown in Table 2.

[0052] 4. Regulate the selection of coal types;

[0053] According to steps 1 to 3, the average maximum reflectance of vitrinite and the content of coal rock micro-components of the regulated coal types (including high metamorphic coal, low activity coal and low metamorphic coal) are tested respectively. According to the relationship between the metamorphic degree (V-Step) and the optimal activity-inertness ratio (such as Figure 1 As shown), calculate the mass corresponding to the ideal inert group content.

[0054] 5. Coal blending coking experiment;

[0055] Taking a 40kg experimental coke oven (the present invention is not limited to this volume experimental coke oven) as an example, the amount of ultra-high vitrinite coking coal and the controlled coal type is calculated according to the amount of coal entering the oven of 45kg. Taking high metamorphic coal and ultra-high vitrinite coking coal A as examples, all components in the high metamorphic coal are inert substances, and 15.53kg of high metamorphic coal and 29.47kg of ultra-high vitrinite coking coal A are added to carry out a binary coal blending coking experiment.

[0056] The particle size of the inert material has an important influence on the coke strength and pore development of the coke. The present invention preferably uses a double-roll crusher (a jaw crusher, a hammer crusher, etc. may also be used) to screen each regulated coal at 1.0 mm and 0.50 mm, and then mixes regulated coal of 0.5-1.0 mm particle size and less than 0.50 mm particle size in a ratio of 1:2.

[0057] 6. Inspection of coal blending effect;

[0058] After the coal blending experiment is completed, representative coke blocks are selected and crushed to a particle size less than 1 mm. Then, fine particles with a particle size of <0.1 mm are screened out (the optical structure is not easy to distinguish under a microscope), and 0.1-1.0 mm particle size coke samples are taken and mixed with a binder to form a molding block (diameter ≥ 20 mm). Coke optical slices are prepared by coarse grinding, fine grinding and polishing.

[0059] Place the coke sheet under a reflected polarized light microscope, insert a gypsum test board (wavelength 1λ) under orthogonal polarized light, and use an oil-immersed objective to observe the coke interface bonding and microscopic characteristics. The coal with good coke interface bonding and small pores is considered to have better compatibility.

[0060] 7. Industrial production verification;

[0061] The ultra-high vitrinite coking coal and the regulated coal are mixed according to the proportion to form the test coal. Industrial coal blending experiments are carried out according to the corresponding coal types to verify the production and use effects.

[0062] In order to more intuitively embody the present invention, the embodiments of the present invention are further described in conjunction with examples. The following examples are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any technical solution that can be obviously obtained by a person skilled in the art within the technical scope disclosed in the present invention, including simple changes or equivalent replacements, is within the protection scope of the present invention.

[0063] [Example 1]

[0064] In this embodiment, the vitrinite reflectance, reflectance distribution and micro-component content of ultra-high vitrinite coking coal A are shown in Tables 1 and Figure 2 As shown, the vitrinite content of ultra-high vitrinite coking coal A is as high as 98.2%.

[0065] Table 1 Coal petrological characteristics of ultra-high vitrinite coking coal A

[0066]

[0067] According to the coal-rock blending theory, high-metamorphic coal is completely inert. According to the metamorphic degree of ultra-high vitrinite coking coal A The ideal inert component content is calculated to be 37.58%, as shown in Table 2. Based on a sample weight of 45 kg, assuming that the mass of the added high-metamorphic coal (inert matter) is y, then:

[0068] y+0.047×(45-y)=45×0.3758…Equation (1)

[0069] y=15.53kg.

[0070] Table 2 Calculation of ideal inert component content of ultra-high vitrinite coking coal A

[0071] Vitrinite reflectance range / % Active ingredient content / % Optimum active-inert ratio Ideal inert component content / % 0.70-0.80 7.2 3 2.40 0.80-0.90 44.9 2.8 16.04 0.90-1.00 35.4 2.5 14.16 1.00-1.10 12.2 2.5 4.88 1.10-1.20 0.3 2.9 0.10 total - - 37.58

[0072] The particle size of inerts has an important influence on the coke strength and pore development of coke. In this embodiment, a double-roll crusher is used to screen high-metamorphic coal at 1.0 mm and 0.50 mm. 5.80 kg of sample coal with a particle size of 0.5-1.0 mm and 9.73 kg of sample coal with a particle size less than 0.50 mm are added to 29.47 kg of ultra-high vitrinite coking coal A for a binary coal blending experiment.

[0073] A 40kg side-loaded experimental coke oven was used to carry out coking experiments on ultra-high vitrinite coking coal A and blended coal (high metamorphic coal) according to the experimental procedures, and the strength of the prepared coke was tested. The results are shown in Table 3.

[0074] Table 3 Coke quality characteristics of ultra-high vitrinite coking coal A after coking alone and coking with high metamorphic coal

[0075]

[0076] As shown in Table 3, after adding high metamorphic coal, the cold strength of coke made from the blended coal is slightly reduced, while the hot strength and reactivity are improved. Specifically, the coke thermal reactivity CRI reaches 26.7%, which is 13.7% lower than that of ultra-high vitrinite coking coal A alone, and the coke thermal reaction strength CSR reaches 50.2%, which is 13.4% higher than that of ultra-high vitrinite coking coal A alone. The coke strength is improved.

[0077] The optical structure characteristics of coke prepared by coking ultra-high vitrinite coking coal A alone are as follows Figure 8a , Figure 8b As shown in (oil immersion, orthogonal polarization, 1λ test plate, 500 times), the optical structure characteristics of coking coal A with high metamorphic coal are as follows Figure 3a , Figure 3b As shown (oil immersion, orthogonal polarization, 1λ test plate, 500 times). The crushing particle size of high metamorphic coal is small, and the amount added is low, so it can be fully mixed with ultra-high vitrinite coking coal A. In the coke prepared by adding these two kinds of coal, the active components in ultra-high vitrinite coking coal A have a better "wrapping" effect on the high metamorphic coal particles, and the high metamorphic coal particles can play a "skeleton" role, which has a certain improvement on the coke strength.

[0078] A coking plant has four 52-hole JNX70-2 type reheating type 7-meter top-loading coke ovens, and a supporting 3×160t / h dry quenching unit, with an annual coke production of 2.55 million tons. Based on the current coking production ratio, ultra-high vitrinite coking coal A and high metamorphic coal were added to conduct a coal blending coking test, as shown in Table 4.

[0079] Table 4 Coal blending scheme for coking test

[0080]

[0081] According to the relevant national standards, the ash content, volatile matter, total sulfur, bonding index and gelatinous layer index of the blended coal were tested respectively, and a 7-meter top-loading coke oven was used for coking; according to the relevant national standards, the crushing strength M40, abrasion resistance M10, thermal reactivity CRI and post-reaction strength CSR of the dry quenched coke were tested. The quality indicators of the blended coal and coke are shown in Table 5.

[0082] Table 5 Coal blending and coke quality with ultra-high vitrinite coking coal A

[0083]

[0084] As shown in Table 5, the ash content of the blended coal in Example 1 is slightly reduced, while the sulfur content, volatile matter yield, bonding index, maximum thickness of the gelatinous layer (Y value), and final shrinkage (X value) remain basically unchanged. After adding the blended coal, the crushing strength M40, wear resistance M10, and thermal reactivity CRI of the coke remain basically unchanged, but the post-reaction strength CSR is slightly improved.

[0085] Conclusion: Under the existing coal blending conditions, adding ultra-high vitrinite coking coal A for coal blending and coking can meet the metallurgical coke standards for blast furnaces, basically ensure the stability of coke quality, and significantly reduce the coal blending cost.

[0086] [Example 2]

[0087] In this embodiment, the vitrinite reflectance, reflectance distribution and micro-component content of ultra-high vitrinite coking coal B are shown in Tables 6 and Figure 4 As shown in Figure 2, the vitrinite content of ultra-high vitrinite coking coal B is as high as 97.6%.

[0088] Table 6 Coal petrological characteristics of ultra-high vitrinite coking coal B

[0089]

[0090] The optical structure characteristics of coke prepared by coking ultra-high vitrinite coking coal B alone are as follows Figure 9a , Figure 9bAs shown (oil immersion, orthogonal polarization, 1λ test plate, 500 times); according to the calculation method of Example 1, ultra-high vitrinite coking coal B and low activity coal were blended in a ratio of 7:3 for coking experiments, and the optical structure characteristics of the coke are as follows Figure 5a , Figure 5b As shown (oil immersion, orthogonal polarization, 1λ test plate, 500 times). Ultra-high vitrinite coking coal B has a good encapsulation of low-activity coal, and there are no large pores in the coke particles. The low-activity coal particles are embedded in the ultra-high vitrinite coking coal B particles, the pore walls are relatively thick, and the bonding interface between the particles is not obvious.

[0091] A coking plant has four 52-hole JNX70-2 type reheating type 7-meter top-loading coke ovens, and a supporting 3×160t / h dry quenching unit, with an annual coke production of 2.55 million tons. On the basis of the current coking production ratio, ultra-high vitrinite coking coal B and low-activity coal were added to conduct a coal blending coking test (see Table 7).

[0092] Table 7 Coal blending scheme for coking test

[0093]

[0094] In accordance with relevant national standards, the ash content, volatile matter, total sulfur, bonding index and gelatinous layer index of the blended coal are tested respectively, and coking is carried out in a 7-meter top-loading coke oven; in accordance with relevant national standards, the crushing strength M40, abrasion resistance M10, thermal reactivity CRI and post-reaction strength CSR of the dry quenched coke are tested.

[0095] The quality indicators of blended coal and coke are shown in Table 8.

[0096] Table 8 Coal blending and coke quality with ultra-high vitrinite coking coal B

[0097]

[0098] As shown in Table 8, the ash content and sulfur content of the blended coal in Example 2 are reduced, the volatile matter yield and bonding index are slightly increased, the maximum thickness of the gelatinous layer (Y value) is slightly increased, and the final shrinkage (X value) is basically unchanged. After adding the blended coal, the crushing strength M40, wear resistance M10 and thermal reactivity CRI of the coke remain basically unchanged, but the post-reaction strength CSR is slightly improved.

[0099] Conclusion: Under the existing coal blending conditions, the addition of ultra-high vitrinite coking coal B for coal blending can meet the metallurgical coke standards for blast furnaces, basically ensure the stability of coke quality, and significantly reduce the coal blending cost.

[0100] [Example 3]

[0101] In this embodiment, the vitrinite reflectance, reflectance distribution and micro-component content of ultra-high vitrinite coking coal C are shown in Tables 9 and Figure 6 As shown in Figure 1, the vitrinite content is as high as 97.4%.

[0102] Table 9 Coal petrological characteristics of ultra-high vitrinite coking coal C

[0103]

[0104] The optical structure characteristics of coke prepared by coking ultra-high vitrinite coking coal C alone are as follows Fig.10a , Fig.10b As shown in (oil immersion, orthogonal polarization, 1λ test plate, 500 times), according to the calculation method of Example 1, ultra-high vitrinite coking coal C and low metamorphic coal are mixed in a ratio of 6:4 to carry out a coal blending coking experiment. The optical structure characteristics of the coal blended coke are as follows Figure 7a , Figure 7b As shown (oil immersion, crossed polarizers, 1λ test plate, 500x).

[0105] As shown in Figure 7, the ultra-high vitrinite coking coal C has a better encapsulation of low-metamorphic coal, and the pore wall is thicker; the low-metamorphic coal particles are embedded in the ultra-high vitrinite coking coal C particles, and the bonding interface is not obvious. However, the distribution uniformity of low-metamorphic coal particles is not good, resulting in large pores in the coke.

[0106] A coking plant has four 52-hole JNX70-2 type reheating type 7-meter top-loading coke ovens, and a supporting 3×160t / h dry quenching unit, with an annual coke production of 2.55 million tons. On the basis of the current coking production ratio, ultra-high vitrinite coking coal C and low metamorphic coal were added to conduct a coking test (see Table 10).

[0107] Table 10 Coal blending scheme for coking test

[0108]

[0109] In accordance with relevant national standards, the ash content, volatile matter, total sulfur, bonding index and gelatinous layer index of the blended coal are tested respectively, and coking is carried out in a 7-meter top-loading coke oven; in accordance with relevant national standards, the crushing strength M40, abrasion resistance M10, thermal reactivity CRI and post-reaction strength CSR of the dry quenched coke are tested respectively.

[0110] The quality indicators of blended coal and coke are shown in Table 11.

[0111] Table 11 Coal blending and coke quality using ultra-high vitrinite coking coal C

[0112]

[0113] As shown in Table 11, the ash content and sulfur content of the blended coal in Example 3 are reduced, the volatile matter yield and bonding index are slightly increased, the maximum thickness of the gelatinous layer (Y value) is slightly increased, and the final shrinkage (X value) is basically unchanged. After adding the blended coal, the crushing strength M40 and the post-reaction strength CSR of the coke are slightly improved, and the wear resistance M10 and thermal reactivity CRI are slightly reduced.

[0114] Conclusion: Under the existing coal blending conditions, the addition of ultra-high vitrinite coking coal C for coal blending can meet the metallurgical coke standards for blast furnaces, basically ensure the stability of coke quality, and significantly reduce the coal blending cost.

[0115] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for coking coal blending by adding ultra-high vitrinite coking coal, characterized in that: The steps include: 1) Determine the average maximum reflectance of vitrinite and draw a reflectance distribution diagram; 2) Quantitative analysis of coal and rock microscopic components; Determine the contents of vitrinite V, inertinite I and exinite E in ultra-high activity coking coal; 3) Calculation of coal-rock blending parameters; According to the metamorphic degree R of ultra-high vitrinite coking coal r o an Calculate the ideal inert component content; 4) Regulate the selection of coal types; The regulated coal types are divided into high metamorphic coal, low activity coal and low metamorphic coal. Each type of regulated coal is subjected to steps 1) to 3) to measure the average maximum reflectance of vitrinite and the content of microscopic components of coal rock, and the mass corresponding to the ideal inertinite content is calculated according to the relationship between the degree of metamorphism and the optimal activity-inertinite ratio; 5) Coal blending coking experiment; Using experimental coke ovens, ultra-high vitrinite coking coal and one of the regulated coals were blended, and binary blending coking experiments were conducted. The blending amounts of ultra-high vitrinite coking coal and regulated coal were calculated according to the amount of coal fed into the furnace. 6) Coal blending effect inspection; After the coal blending experiment is completed, select representative coke blocks, crush them to a particle size of less than 1.0 mm, then screen out fine particles with a particle size of less than 0.1 mm, take coke samples with a particle size of 0.1 to 1.0 mm and mix them with a binder to make blocks with a diameter of ≥ 20 mm, and prepare coke slices through coarse grinding, fine grinding and polishing; place the coke slices under a reflected polarizing microscope, insert a gypsum inspection board under orthogonal polarization, and use an oil-immersed objective to observe the coke interface bonding and microscopic characteristics. The coke with good interface bonding and small pores is regarded as a coal with good compatibility; 7) Industrial production verification; The ultra-high vitrinite coking coal and the regulated coal are mixed according to the proportion and used as the test coal. Industrial coal blending experiments are carried out according to the corresponding coal types to verify the production and use effects.

2. The method for coking coal blending by adding ultra-high vitrinite coking coal according to claim 1, characterized in that: In the step 1), according to GB / T 6948-2008 "Method for Microscopic Determination of Vitrinite Reflectance of Coal", the maximum reflectance of the vitrinite of ultra-high activity coking coal is tested, the number of test points is not less than 100, and the mean μ and standard deviation σ of the test data are calculated; the average maximum reflectance of the vitrinite R m o ax =μ; taking the reflectivity interval of 0.10% as the step, the percentage content of the measuring points in each step is counted, and the vitrinite reflectivity distribution diagram is drawn.

3. The method for coking coal blending by adding ultra-high vitrinite coking coal according to claim 1, characterized in that: In the step 5), when conducting the binary coal blending experiment, the regulated coals are first crushed and screened, and regulated coals with a particle size of 0.5-1.0 mm and less than 0.50 mm are blended in a mass ratio of 1:2.

Citation Information

Cited By

  • Coking coal active component classification efficiency correction method

    CN122385854A

  • Method for correcting classification efficiency of coking coal active component

    CN122385854B